The Impact of Scrabble Game on EFL Context: Students Interpretation Ability in Vocabulary - Waliyudin; Annisah; Nashruddin (Eduvelop: Journal of English Education and Development, 2026)
This study investigates the effect of the Scrabble teaching method on students’ vocabulary interpretation ability in English instruction for English as a Foreign Language (EFL) students at SMAN 1 Kota Bima. Using a quantitative pre-experimental approach with a one-group pretest–posttest design, the study involved class XI IPA. Data were collected through vocabulary interpretation tests administered before and after the implementation of the Scrabble teaching method. The findings reveal that the application of the Scrabble teaching method significantly improves students’ ability to interpret the meaning of English vocabulary by promoting active participation, collaborative learning, and contextual engagement. The effectiveness of the method was supported by appropriate instructional procedures and teaching techniques. However, the findings also indicate that the success of the implementation is highly dependent on teachers’ pedagogical competence in managing classroom activities and integrating game-based instruction effectively. The study concludes that, with proper instructional planning and teacher expertise, the Scrabble teaching method has strong potential to enhance vocabulary interpretation ability and enrich students’ overall learning experience in EFL classrooms.